Exe txt - Snelson, Daniel (GPDF editions, 2015)
Danny Snelson’s EXE TXT is the attempt to make a database of texts theorize itself. The project makes use of the texts accessible as textwarez on Textz.com, a website run by Sebastian Lütgert between 2000 and 2004 that hosted around 831 text files "[r]anging from experimental poetry and cyberpunk fiction to media theory and political tracts." Snelson used a Python script on this corpus to extract sentences containing variants of the strings "text" and "software" (including their translations) to find out "how text might meet software within the works that Textz hosts." ...
Keywords: Soziales Netzwerk; Bioinformatik; Künstlerbuch